PENGARUH MANAJEMEN ASET DAN SISTEM INFORMASI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI EMPIRIS PADA KANTOR BPKAD KOTA AMBON) - Kona, Mindriyanti; Sapulette, Shella Gilby; Lewaru, Trisna Sary (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
This study aims to examine the effect of Asset Management and the RegionalFinancial Information System on the Quality of Financial Reports. It is aquantitative research with data collection methods using questionnaires, and theanalysis technique used is multiple linear regression analysis. The testing wasconducted using the SPSS Version 25 application. The subjects of this study areall employees working at the BPKAD (Regional Financial and Asset ManagementAgency) in Ambon City, with a sample of 50 respondents. The sampling was doneusing saturated sampling. The results of the study indicate that AssetManagement and the Regional Financial Information System have a positive andsignificant effect on the Quality of Financial Reports.